A Preliminary Study on Pteridophyte of Lombok: List of the Species - Wardani, Wita; Jaenudin, Jaenudin (Proceeding International Conference on Global Resource Conservation, 2013)
The last publication on fern of Lombok that was able to be retrieved is written on 1939.Â The account, compiled by Dr. O. Posthomus, is listing all fern species recorded in some important herbarium, for Southeast Asia at the time, collected from the Lesser Sunda Islands. Since this publication, we have not found works to renew it. This paper present an update on the list of the pteridophyte species from Lombok, with additional information on the taxonomical status and some of their ecological preferences.Â Keywords: Lombok, Pteridophyte, updated list